Новые представители трематод семейства Acanthocolpidae Luhe, 1909, обнаруженные у промысловых рыб Южной Атлантики - Парухин, А.М. (Вестник зоологии, 1968)
Two new species of Trematoda are described in the article: Stephanostomunz solontschenki sp. n. and S. kovalevi sp. n. from the food-fish of the South Atlantic, where the author investigated the fish parasitofauna in Wallfish-Bay region in 1965.